2019
DOI: 10.1103/physrevb.99.045420
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced magneto-optical response due to the flat band in nanoribbons made from the αT3 lattice

Abstract: We study the optical response of nanoribbons made from the α−T3 lattice under a weak magnetic field in the terahertz to far-infrared regime. It is found that the magnetic field can open a gap in the band structure and induce a new absorption peak with much reduced frequency in metallic armchair ribbons and a class of zigzag ribbons with particular boundaries. This tunable magnetooptical modulation effect is attributed to the interband transitions between the flat band and the propagating bands. By contrast, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 46 publications
(46 reference statements)
8
39
1
Order By: Relevance
“…As a consequence, the eigenvalues vary differently when B is increased. Such valley-anisotropy has been found in the magneto-optical properties of (zigzag) α − T 3 nanoribbons [34].…”
Section: Eigenvalue Problem Of the α − T 3 Quantum Dot In A Perpendicmentioning
confidence: 68%
See 1 more Smart Citation
“…As a consequence, the eigenvalues vary differently when B is increased. Such valley-anisotropy has been found in the magneto-optical properties of (zigzag) α − T 3 nanoribbons [34].…”
Section: Eigenvalue Problem Of the α − T 3 Quantum Dot In A Perpendicmentioning
confidence: 68%
“…Most notably, the flat band crosses the nodal Dirac points, which has peculiar consequences, such as an α-dependent Berry phase [30], super-Klein tunnelling [31,32], or Weiss oscillations [33]. Interestingly, the magneto-optical response will be also enhanced due to the flat bands [34]. Analysing the frequencydependent magneto-optical and zero-field conductivity of Hg 1−x Cd x Te [35] at the critical cadmium concentration x c 0.17 (marking the semimetal-semiconductor transition), it has been shown that this material can be linked to the α − T 3 model with α = 1/ √ 3 [36].…”
Section: Introductionmentioning
confidence: 99%
“…The dice lattice is a honeycomb lattice with an additional sublattice placed at the hexagonal center, and the additional sublattice is coupled to the three sublattices of the original honeycomb lattice [54]. The couplings of the dice lattice are uniform in contrast to the α-T 3 lattice with distinct couplings from the hexagonal vertexes to the hexagonal center [62][63][64][65][66][67]. The dice lattice under consideration shown in Fig.…”
Section: Dice Latticementioning
confidence: 99%
“…For highest (or lowest) band in the Brillouin Zone, there exists two Dirac points, which closely attach to the flat band. Following the discovery of this new material, a lot of novel physical phenomena, for example, Hofstadter butterfly effect 30 , magneto-optical conductivity 31 , Super-Klein tunneling 32 , zitterbewegung effect 33 , magnetism 34 , and magnetoconductivity 35,36 , etc., have attracted great interests.…”
Section: Introductionmentioning
confidence: 99%